Studying the frictional force directions via bristles - S. Prasitpong (2018)
We present simple apparatus designed to help Thai high school students visualize the directions of frictional forces. Bristles of toothbrushes, paintbrushes and scrubbing brushes are used to demonstrate the frictional forces acting in a variety of situations. These demonstrations, when followed by discussion of free-body diagrams, were found to be effective in teaching frictional force directions. © 2010 IOP Publishing Ltd.